Characteristics and Prognosis of Patients With Left-Sided Native Bivalvular Infective Endocarditis - Bohbot, Yohann; Peugnet, Fanny; Lieu, Audrey; Carbone, Andreina; Mouhat, Basile; Philip, Mary; Gouriet, Frederique; Arregle, Florent; Chevalier, Florent; Diouf, Momar; Rusinaru, Dan; Habib, Gilbert; et al. (Canadian journal of cardiology, 2021)
Most cases of left-sided native valve infective endocarditis (IE) involve a single valve and little is known concerning IE that simultaneously affects the aortic and mitral valves. We aimed to determine the characteristics, identify the prognostic factors, and define the effect of early surgery for patients with left-sided native bivalvular IE. This analysis included 1340 consecutive patients who presented with definite acute left-sided native valve IE in a 2-centre cohort study. A bivalvular involvement was present in 257 patients (19%). Patients with bivalvular IE had more embolic events (P = 0.044), congestive heart failure (P = 0.016), vegetations, and perivalvular complications (both P < 0.001) than those with monovalvular IE. Early surgery was more frequent for patients with bivalvular IE (P < 0.001). Thirty-day mortality was higher for patients with bivalvular IE than for those with monovalvular IE (24.5% vs 17.6%; P = 0.008), even after adjustment (odds ratio, 1.86 [95% confidence interval, 1.26-2.73]; P < 0.001). Estimated 10-year survival was 70% ± 1% for monovalvular IE and 59% ± 3% for bivalvular IE (P = 0.002). Bivalvular IE was still associated with mortality in multivariable Cox analysis, after adjustment for covariates including age, neurological events, congestive heart failure, Staphylococcus spp infection, perivalvular complications, and early surgery (hazard ratio, 1.70 [95% confidence interval, 1.31-2.11]; P < 0.001). Early surgery was associated with increased survival for patients with bivalvular IE (79% ± 4% vs 35% ± 6%; P < 0.001). Bivalvular involvement is frequent in left-sided native valve IE, is associated with more embolic events and congestive heart failure than monovalvular IE, and patients are at a high risk of death. Early surgery is associated with improved survival and should be systematically discussed in the absence of contraindication. La plupart des cas d’endocardite infectieuse (EI) sur valve native gauche sont concernés par une seule valve. On en connaît peu sur l’EI qui touche simultanément les valves aortique et mitrale. Nous avions pour objectif de déterminer les caractéristiques, les facteurs pronostiques et les répercussions de l’intervention chirurgicale précoce chez les patients atteints d’une EI bivalvulaire native gauche. La présente analyse portait sur 1 340 patients consécutifs qui s’étaient présentés à une étude de cohorte de deux centres en raison d’une indéniable EI sur valve native gauche. Une atteinte bivalvulaire était présente chez 257 patients (19 %). Les patients atteints d’une EI bivalvulaire avaient davantage de maladies emboliques (P = 0,044), d’insuffisance cardiaque congestive (P = 0,016), de végétations et de complications périvalvulaires (les deux P < 0,001) que ceux atteints d’une EI monovalvulaire. L’intervention chirurgicale précoce était plus fréquente chez les patients atteints d’EI bivalvulaire (P < 0,001). La mortalité à 30 jours était plus élevée chez les patients atteints d’EI bivalvulaire que chez ceux atteints d’EI monovalvulaire (24,5 % vs 17,6 %; P = 0,008), même après l’ajustement (ratio d’incidence approché, 1,86 [intervalle de confiance à 95 %, 1,26-2,73]; P < 0,001). La survie estimée à 10 ans était de 70 % ± 1 % lors d’EI monovalvulaire et de 59 % ± 3 % lors d’EI bivalvulaire (P = 0,002). À l’analyse multivariée selon le modèle de Cox, l’EI bivalvulaire était encore associée à la mortalité après l’ajustement des covariables, y compris l’âge, les accidents neurologiques, l’insuffisance cardiaque congestive, l’infection à Staphylococcus spp, les complications périvalvulaires et l’intervention chirurgicale précoce (rapport de risque, 1,70 [intervalle de confiance à 95 %, 1,31-2,11]; P < 0,001). L’intervention chirurgicale précoce était associée à une survie accrue chez les patients atteints d’EI bivalvulaire (79 % ± 4 % vs 35 % ± 6 %; P < 0,001). L’atteinte bivalvulaire est fréquente lors d’EI sur valve native gauche, est associée à davantage de maladies emboliques et d’insuffisance cardiaque congestive que l’EI monovalvulaire. De plus, les patients sont exposés à un risque élevé de décès. L’intervention chirurgicale précoce est associée à une meilleure survie et devrait systématiquement faire l’objet de discussions en l’absence de contre-indications.